High Sensitivity of HSA Capacitive Immunosensor using Poly-para-phenylenediamine Modified Gold Electrode - Thipmanee, Orawan (YRU Journal of Science and Technology, 2018)
The highly sensitive capacitive immunosensor detects the capacitance change at the electrode-electrolyte interface when the immobilized antibody on the electrode surface binds to the antigen in the sample. One of the important steps for the construction of the capacitive sensor is the immobilization of antibody via an insulating layer on the electrode surface. This layer is generally based on a self-assembled monolayer (SAM) of alkanethiol compounds, however, the self-assembling process requires a relatively long period of time. In this work electropolymerization of para-phenylenediamine (p-PD) on the gold electrode surface was investigated as an alternative for the immobilization of antibodies. Anti-human serum albumin (anti-HSA) was immobilized for the capacitive detection of HSA with the flow system. Both concentration of the monomer solution and the number of electropolymerization scan were optimized. Under the optimized conditions, a wide linear concentration range, 1.0x10 -15 to 1.0x10 -10 M, was obtained with a very low detection limit of 1.0x10 -15 M. This sensor could be reused up to 31 times with relative standard deviation (RSD) lower than 3.0%. Moreover, an easy and very fast of the poly-para-phenylenediamine (PpPD) modified a gold electrode was obtained.